Bassic Movement Dancing Skills of 5-6 Years Old Children Through Dance and Sing Theme Based Learning with Demonstration Method (Universitas Negeri Semarang, 2019)
This study has purpose to analyze of bassic movement dancing skills of 5-6 years old children through dance and sing theme based learning with demonstration method in PAUD Sekar Nagari and TK Pertiwi 49 Semarang. This study applied an experimental method with factorial experimental design. Data collection method used was observation by using research instruments sheet. The sampling technique used in this study was purposive sampling and therefore obtained 40 students as the sample of the study which were divided into two groups, 10 male and 10 female in the experimental group and the control group respectively. In the experimental group uses direct demonstration method and in the control group uses indirect demonstration method. The data was analyzed by using two-ways ANOVA test by using SPSS 17.0 and with significance level of 5%. The results of this study showed that there is a the improvement of bassic movement dancing skills of 5-6 years old children through dance and sing theme based learning with demonstration method. The conclusions of this study are: (1) the development of the fundamental movement skill of male students is higher than that of the female students; (2) the demonstration method can directly give better effect to the fundamental movement skills compared to demonstration through video; (3) there is a positive relationship between demonstration method and gender of the children on their bassic movement dancing skills.